2018
DOI: 10.1186/s13024-018-0294-0
|View full text |Cite
|
Sign up to set email alerts
|

Disease-modifying effects of metabolic perturbations in ALS/FTLD

Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) are two fatal neurodegenerative disorders with considerable clinical, pathological and genetic overlap. Both disorders are characterized by the accumulation of pathological protein aggregates that contain a number of proteins, most notably TAR DNA binding protein 43 kDa (TDP-43). Surprisingly, recent clinical studies suggest that dyslipidemia, high body mass index, and type 2 diabetes mellitus are associated with better clinical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 200 publications
1
22
0
Order By: Relevance
“…Future research should encourage approaches that test convergent biologically plausible mechanisms. For example, the transactive response DNA binding protein 43 (TDP-43) has been implicated in the etiology of several aging-related neurodegenerative disorders, including PD [138], AD [127], ALS [86], frontotemporal dementia [18], and idiopathic late-onset dementia [123].…”
Section: Resultsmentioning
confidence: 99%
“…Future research should encourage approaches that test convergent biologically plausible mechanisms. For example, the transactive response DNA binding protein 43 (TDP-43) has been implicated in the etiology of several aging-related neurodegenerative disorders, including PD [138], AD [127], ALS [86], frontotemporal dementia [18], and idiopathic late-onset dementia [123].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, ALS patients with high body mass index (BMI) have better prognosis than patient with BMI within the normal values. Moreover, obese individuals are less likely to develop ALS than individuals with average weight (Jawaid et al, 2018). However, BMI does not differentiate between fat or lean body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Other intriguing lines of research evaluated some metabolic parameters as disease-modifiers that can impact the clinical course in ALS. For example, recent investigations have shown that high-risk cardiovascular profiles such as a high body mass index (BMI) or diabetes mellitus type 2 might be protective for ALS patients and may act by delaying the onset and/or by slowing down clinical progression of the disease [79][80][81][82][83][84][85]. Altogether, these finding suggest that caution should be exercised when comorbidities and risk factors are evaluated as prognostic factor in such as complex diseases as ALS and FTD.…”
Section: Disease Modifier Factorsmentioning
confidence: 99%
“…Altogether, these finding suggest that caution should be exercised when comorbidities and risk factors are evaluated as prognostic factor in such as complex diseases as ALS and FTD. In particular, a better characterization of the eventual association between the clinicopathological features of the patients and a particular metabolic disorder might be helpful to understand if and how metabolic disorders can influence the subcellular localization, aggregation, and phosphorylation of some of pathogenic proteins, or if the metabolic disorders might rather modulate the toxic effects downstream of these events [81]. In addition, these observations open potentially the way to nutrition, dietary supplements (in particular, antioxidant) and lifestyle interventions as potential strategies for modifying the course of the disease [86][87][88].…”
Section: Disease Modifier Factorsmentioning
confidence: 99%